Higher precision constraints on the tau $$g-2$$ g - 2 in LHC photon-initiated production: a full account of hadron dissociation and soft survival effects - L. A. Harland-Lang (European Physical Journal C: Particles and Fields)
Abstract We present the first calculation of photon-initiated $$τ $$ τ pair production in the presence of non-zero anomalous magnetic ( $$a_τ $$ a τ ) and/or electric dipole ( $$d_τ $$ d τ ) moments of the $$τ $$ τ lepton that accounts for the non-trivial interplay between these modifications with the soft survival factor and the possibility of dissociation of the hadron (proton or ion) beam. The impact of these is on general grounds not expected to have a uniform dependence on the value of $$a_τ , d_τ $$ a τ , d τ , but in all previous analyses this assumption has been made. We have therefore investigated the importance of these effects in the context of photon-initiated $$τ $$ τ pair production in both pp and PbPb collisions. This is in general found to be relatively small, at the percent level in terms of any extracted limits or observations of $$a_τ , d_τ $$ a τ , d τ , such that these effects can indeed be safely ignored in existing experimental analyses. However, as the precision of such determinations increases in the future, the relevance of these effects will likewise increase. With this in mind we have made our calculation publicly available in the SuperChic Monte Carlo generator, including the possibility to simulate this process for varying $$a_τ , d_τ $$ a τ , d τ without rerunning.